Состояние гемостаза при различных видах обезболивания - Клигуненко, Е.Н.; Доценко, В.В. (Досягнення біології та медицини, 2012)
Изучено влияние различных методик анестезии на состояние гемостаза при плановых абдоминальных операциях. Выявлено снижение риска тромбоопасности при использовании регионарной анестезии, опосредованное уменьшением активации общего пути свертывания и снижением интенсивности фибринолиза. Тhe effect of different methods of anesthesia on the state of hemostasis during elective abdominal operations was studied. A reduction of the risk of thrombotic threat after regional anesthesia was detected, which was mediated with a decrease in activation of the general pathway coagulation and decrease in the intensity of fibrinolysis.